The diagnostic value of combined pulmonary function test and exhaled nitric oxide monitoring in cough variant asthma with or without gastroesophageal reflux disease: a retrospective study - Sen Li; Siyao Xu; Yuan Yang; Zhe Wang; Yaru Hou (BMC Pulmonary Medicine)
Abstract Introduction This study aimed to investigate the effect of fractional exhaled nitric oxide (FeNO), a marker of airway inflammation, together with small airway function tests in diagnosing cough variant asthma (CVA), particularly in patients with gastroesophageal reflux disease (GERD). Methods This retrospective cohort study included adult patients with chronic cough for more than eight weeks who were divided into a CVA group and a control group. Participants underwent pulmonary function tests and FeNO measurements. Statistical tests and ROC curve analysis were used to assess diagnostic accuracy. Results CVA patients had higher FeNO levels than controls, regardless of with or without GERD. There were no significant differences in FEV1, FVC, and FEV1/FVC ratio between the control and CVA groups, but CVA patients had significantly lower MEF25, MEF50, MEF75, and MMEF values. FeNO was negatively correlated with MEF50, MEF75, and MMEF. The AUC of FeNO in diagnosing CVA was 0.862. Combining FeNO with MMEF resulted in the highest diagnostic accuracy (AUC = 0.909). The diagnostic benefits of FeNO and FeNO + MMEF were similar in GERD patients. Conclusion Combining FeNO with small airway function tests, especially MMEF, can improve the diagnostic accuracy of CVA, while FeNO and FeNO + MMEF performed similar diagnostic accuracy in patients with GERD. Clinical trial number Not applicable.